Microperforations in benthonic foraminifers from Lagoa da Pitanguinha, RJ - Cardoso, Mariana; Batista, Daniele da Silva; Damazio, Cynthia; Senra, Maria Célia Elias (Anuário do Instituto de Geociências, 2007)
Abstract